Courage in Charles Dickens A Tale of Two Cities - Anggaseng, Sindy; Wuntu, Ceisy N.; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The research is aimed at revealing courage from Charles Darnay in A Tale of Two Cities by Charles Dickens. the story of this novel is describing of France in the griped of masses, In doing research the objective approach is taken because it focuses only on the object material that is A Tale of Two Cities written by Charles Darnay. The data analyzed are presented in descriptive form, are clarified as qualitative research because data is in form of words. Since this study is objected to explore courage, revolution, love and sacrifice of this study. The result show that the courage of Charles Darnay in resisting his fear to help his relatives and family in the revolution. Dickens described the injustice that led to Charles Darnay having to deal with law and justice, He also made revolution, poverty, oppression, misery, hanging, and guillotine became common before the revolution, and France was free from the grip of aristocracy.